Un terrain d’expérimentation au long cours : Robert Lafont et la Revue des langues romanes - Philippe Gardy (Revue des Langues Romanes)
Robert Lafont, a professor at the University of Montpellier, where he spent his entire career in higher education, was for many years (between 1964 and 2004) a regular contributor to the Revue des langues romanes, a publication to which he was attached, beyond obvious scientific motivations, by more personal circumstances, of which only a few elements have been evoked here, not the least of which was his commitment, following the example of his teacher and friend Charles Camproux, in favor of the Occitan language. This no doubt explains why Lafont made the RLaR, in the long run, the place of experimentation for his own research. The inventory and periodization of his collaborations allow us to sketch a portrait, the time having passed, of an original personality, between medievalism, linguistics, Occitan literary history and cultural anthropology.